The Implications of Corporate Social Responsibility on the Accounting Profession: The Case of Romania - Nadia Albu; Cătălin Nicolae Albu; Maria Mădălina Gîrbină; Maria Iuliana Sandu (Amfiteatru Economic Journal, 2011)
Corporate social responsibility and sustainability are key issues in the current business environment. Accountants play a crucial role in organizations in areas closely related to corporate social responsibility such as reporting, transparency, ethics, legal compliance, communication with stakeholders, and resource consumption. The aim of this paper is to analyze the role of accountants within the corporate social responsibility, with an emphasis on the Romanian case. Via literature review and job-offer analysis, we investigate the existence of corporate social responsibility practices in Romania and its implications on the accounting profession. We find that such practices are developed to an incipient but increasing extent in Romania. Romanian accountants are increasingly called to transpose the general framework of CSR, which is legal compliance, communication with stakeholders and performance measurement, thus leading to an increase in the importance of the accounting function in an organization. The following step would be the accountants' involvement in specific actions regarding environmental and social implications, but this is very rare in Romania. We suggest the Romanian higher and professional education adjusts more to the realities of the current business environment.
Keywords: M14; M41; Q01; 330; Corporate Social Responsibility (CSR); accounting profession; Romania; competence; professional body; role of accountants